Farmers' willingness to adopt and accept safe vegetable production in Davao City - Onella, Rona Alynn Q. (Davao City School of Management, University of the Philippines Mindanao, 2016)
Farmers have to produce vegetables which are safe for consumption. Safe vegetable production was developed in countries such as Vietnam in order to regulate pesticide residue as well as lessen input costs for farmers. However, adopting and converting to another farming system such as safe vegetable production can be very risky due to many factors that needs to be considered before venturing into adopting safe vegetable production was assessed by analyzing farmers? perceptions and concerns about farm-level issues. Respondents were local vegetables farmers in Sitio Upian and Mundo Hill in Marilog District, Davao City. The determinants of farmers? adoption decision were analyzed using binary logistic regression and analysis of variance(ANOVA). Results show that most respondents are not aware of safe vegetable production with only 4% who have seen or heard about safe vegetable production. Farm gate price and yield were considered as the most important factors when choosing a farming system. Respondents? perceived a good farming system as a system that is beneficial to farmer health and decreases input costs. Farmers are very concerned about the quality of water they are using and the sanitation of the farm for preharvest stage but they had low levels of concern for postharvest stage except for the proper grading and classification of vegetables. Results of the logistic regression indicate that sex, access to extension services and awareness on organic farming can affect the repondent?s decision to adopt safe vegetable production. Knowledge on the factors influencing the adoption of safe vegetable production is crucial for farming system developers for designing appropriate farming systems with higher likelihood of being adopted.
Thesis (BS Agribusiness Economics)-- University of the Philippines Mindanao, June 2016